Relativistic neoclassical transport coefficients with momentum correction - Marushchenko, I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2017)
The parallel momentum correction technique is generalized for relativistic approach. It is required for proper calculation of the parallel neoclassical flows and, in particular, for the bootstrap current at fusion temperatures. It is shown that the obtained system of linear algebraic equations for parallel fluxes can be solved directly without calculation of the distribution function if the relativistic mono-energetic transport coefficients are already known. The first relativistic correction terms for Braginskii matrix coefficients are calculated. Метод сохранения продольных импульсов обобщён для описания слаборелятивистских электронов. Это необходимо для правильного вычисления продольных неоклассических потоков и, в частности, для бутстреп-тока при термоядерных температурах. Показано, что полученная система линейных алгебраических уравнений для продольных потоков может быть решена непосредственно, без вычисления функции распределения, если релятивистские моноэнергетические коэффициенты уже известны. Получены численные значения для первой релятивистской поправки для вычисления матричных коэффициентов Брагинского. Метод зберігання поздовжніх імпульсів узагальнено для опису слаборелятивістських електронів. Це необхідно для правильного обчислення поздовжніх неокласичних потоків і, зокрема, для бутстреп-струму при термоядерних температурах. Показано, що отримана система лінійних алгебраїчних рівнянь для поздовжніх потоків може бути вирішена безпосередньо, без обчислення функції розподілу, якщо релятивістські моноенергетичні коефіцієнти вже відомі. Отримано числові значення для першої релятивістської поправки для обчислення матричних коефіцієнтів Брагінського.